Monotheism and the Language of Divine Plurality in the Hebrew Bible and the Dead Sea Scrolls - Heiser, Michael S. (Tyndale bulletin, 2014)
Most Hebrew Bible scholars believe that Israelite religion evolved from polytheism to monotheism, an evolution in which the biblical writers participated. The dominant version of this consensus is that this religious evolution culminated by the end of the exile or shortly thereafter. A minority perspective places the evolutionary end point later. At issue is the presence of the language of divine plurality, positive references to other gods (אֱלֹהִים or אֵלִים) under YHWH’s authority, in Jewish religious texts composed during and after the Second Temple period. This article surveys the language of divine plurality in the Hebrew Bible and the sectarian literature at Qumran to show its conceptual continuity and longevity, and rejects the notion that it is incongruent with a belief in the uniqueness of YHWH.